HUBUNGAN PERAN ORANG TUA TERHADAP PERKEMBANGAN PSIKOSOSIAL ANAK USIA SEKOLAH - Eka ' Irmilia; Herlina ' '; Yesi Hasneli3 ' Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract This research conducted to determine the correlation between role of parents among  school-age children’s psychosocial development. The research used the correlation method with cross sectional approach. It was conducted on 75 parents who are in RW 11 villages Tuah Karya sub-district Tampan Pekanbaru by using purposive sampling technique. The research was a questionnaire, observation sheets, and interviews. The analysis used was univariate and bivariate analysis using Chi-Square. The result showed that there was a realationship between the role of parents with school-age children’s psychosocial development with significance of 0,05 is obtained p value < 0,05 it is 0,000. The results of this study expected to be good information for public health teams and parents in order to increasse attention to the development of children , especially in children of school age . Keywords: psychosocial development, role of parents, school-age childrens